SPORTS ORIENTATION AND ITS ESSENCE IN CYCLING - Iv. Kolev (Trakia Journal of Sciences)
The development of sport results in cycling sports, as well as the enormous competition in the sport struggle for global hegemony in cycling disciplines, requires continuous improvement in the quality and effectiveness of the training process. The aim of the following theoretical study is to reveal the characteristic peculiarities and the essence of the sport orientation in the cycling sport. Methods: The research was carried out using the following methods: literary sources study, document analysis, theoretical analysis and synthesis. Results: Analysis. The modern development of cycling is characterized by the deepening of the knowledge of coaches and sport pedagogues in the field of sport orientation, with the creation of objective criteria for the latter, specific to each sport discipline. The choice of the type of sport that corresponds to the individual characteristics and abilities of the individual represents his/her sport orientation. It is primarily related to children’s and adolescent sport. Good sport orientation increases the efficiency of sport selection. Conclusion: Constantly increasing sport performance places ever-increasing demands on cyclists and, in turn, complicates the process of finding talents that combine qualities and abilities that determine success in cycling sports.